The Meaning and Intent of Istitha'ah (Ability to Marry) Perspective of the Shafi'i School - Musyafa , Fikri (Interdisciplinary Journal of Social Science and Education (IJSSE), 2023)
Istitha'ah is an ethic for those who want marriage. In the madhhab of Imam Syafi'i, istitha'ah is the ability of the prospective groom to fulfill the obligations in marriage, such as providing maintenance, protecting the wife, and fulfilling the rights of the wife. The strongest emphasis of the Shafi'i school of thought is on the aspect of the ability to have intercourse. In the present era, the meaning of istitha'ah may not be on the aspect of intercourse, but on the element of ability implicitly, the word means being able to have intercourse accompanied by pre and post-marriage costs.